2020
DOI: 10.1186/s41043-020-00218-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unintended pregnancies among currently married women in Uganda

Abstract: Background Unintended pregnancies are no longer bound to teenagers or school-going children, married women in Uganda, as well do experience such pregnancies though little has been investigated on them. This study examines the determinants of unintended pregnancies among currently married women in Uganda. Methods In this study, we used data from the 2016 Uganda Demographic and Health Survey (UDHS) which comprised of 10,958 married women aged 15–49 years who have ever been pregnant. The analysis was done using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 38 publications
(40 reference statements)
7
33
1
Order By: Relevance
“…This concurred with the findings of Mutumba et al, among Africans and European countries [17]. Previous findings by Wasswa and colleagues revealed that married women in Uganda with higher age at first birth were at an increased risk of unintended pregnancies [40]. In the process of wanting to achieve their desired number of children, women with higher age at first birth may avoid using contraceptives.…”
Section: Discussionsupporting
confidence: 89%
“…This concurred with the findings of Mutumba et al, among Africans and European countries [17]. Previous findings by Wasswa and colleagues revealed that married women in Uganda with higher age at first birth were at an increased risk of unintended pregnancies [40]. In the process of wanting to achieve their desired number of children, women with higher age at first birth may avoid using contraceptives.…”
Section: Discussionsupporting
confidence: 89%
“…This is explained by educated partners having better access to health information and that they are more likely to realize the benefits of HIV testing during pregnancy to prevent HIV transmission and therefore more likely to seek, accept and test for HIV. Educated partners are more likely to have a planned pregnancy [ 67 , 68 ] and this may enable them to think carefully about what the pregnancy requires so that they can mobilize the resources that are needed for maternal services, including PMTCT services. Meaningfully, more than 90% of women in this study reported that their pregnancy was planned and of those, approximately 75% had been tested for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This method had been discussed by numerous authors in literature [ 7 , 8 ]. In this study, we applied a machine learning approach to evaluate various algorithms' performance.…”
Section: Methodsmentioning
confidence: 99%
“…According to a recent DHS survey, the unexpected pregnancy rate in Ethiopia is 28% [ 6 ]. Another study of a Ugandan woman who is currently married found that 37% of pregnancies were unplanned [ 7 ]. Research based on data from six South Asian countries shows that about 28% of married women in Bangladesh have unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation